1995
DOI: 10.3168/jds.s0022-0302(95)76720-0
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Subclinical Mastitis from On-Line Milking Parlor Data

Abstract: A model, based on automatically collected data, was developed for detection of subclinical mastitis. The logistic regression model was based on the following variables: milk electrical conductivity, milk production, parity, and DIM. Subclinical mastitis was defined as a minimal period of 1 wk in which the SCC was > 500 x 10(3) cells/ml. In contrast, periods were defined as healthy if the SCC was < 200 x 10(3) cells/ml. The resulting model had a sensitivity of 55% and specificity of 90% for individual milkings.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
4

Year Published

1998
1998
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 18 publications
0
33
4
Order By: Relevance
“…Thus, one can infer from these results that changes in the paracellular pathway that are caused by the modified apical medium are sufficient to allow for the permeation of albumin into the milk. Both the appearance of albumin and the elevation in electrolytes have been used as clinical measures of mastitis (9,18,23). The fact that milk conductivity is used as an early indicator of mastitis suggests, but does not demonstrate, that changes in milk electrolyte composition precede changes in the epithelial barrier integrity.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, one can infer from these results that changes in the paracellular pathway that are caused by the modified apical medium are sufficient to allow for the permeation of albumin into the milk. Both the appearance of albumin and the elevation in electrolytes have been used as clinical measures of mastitis (9,18,23). The fact that milk conductivity is used as an early indicator of mastitis suggests, but does not demonstrate, that changes in milk electrolyte composition precede changes in the epithelial barrier integrity.…”
Section: Discussionmentioning
confidence: 99%
“…In one study [37], all clinical mastitis cases were found (threshold 500 000 cells/mL plus positive bacteriology) but only 50% from the subclinical cases (> 200 000 cells/mL). In another study [45] when lactation stage, milk yield and parity were taken into consideration, EC showed a sensitivity of 55% to detect subclinical mastitis (threshold > 500 000 or one million cells/mL). For test accuracy it is best to use foremilk.…”
Section: The Electrical Conductivity Of Milkmentioning
confidence: 99%
“…Reneau and Packard (1991) summarized that 70 to 80% of mastitis losses were due to subclinical mastitis. Besides microbiological testing, somatic cell count (SCC) in milk is often used to define subclinical mastitis (Nielen et al, 1995;Deluyker et al, 2005;Gronlund et al, 2005). In addition to established parameters, acute phase proteins (APP) are discussed as being useful in the diagnosis of mastitis.…”
mentioning
confidence: 99%